Optimizing Mechanical Properties of Al6063 Aluminum Alloy through Silicon Weight Percent Variation and Heat Treatment at the Propeller Shaft Materials Casting - Bhiftime, Eka Irianto; Joni, . (Graduate School of Syiah Kuala University, 2024)
Ship propulsion relies significantly on the efficiency of its components, with the shaft propeller playing a pivotal role in navigating vessels through water. Traditionally constructed from steel, this study explores an unconventional approach by employing an Aluminum Alloy base material, specifically the 6063 alloy, for the propeller shaft model. The material's mechanical properties become a crucial focus, prompting a detailed investigation into the impact of silicon and magnesium elements through a meticulous heat treatment process. The experimental procedure involves heating the Al6063 alloy to 790C, transitioning to a complete liquid state, and subsequently incorporating silicon and magnesium at specific temperatures. The stirring process, executed with a mechanical stirrer, sets the stage for the alloy's casting into a mold under pressure. Post-casting, the propeller shaft undergoes a comprehensive heat treatment regimen, including solution treatment, quenching, and artificial aging. The study's findings showcase a remarkable reduction in porosity with increasing silicon elements, reaching its lowest point at 4% wt Silicon. Tensile tests demonstrate a direct correlation between silicon addition and increased stress values, with the highest stress observed at 4% wt Silicon. Concurrently, hardness values ascend proportionally with silicon inclusion, peaking at 4% wt Silicon. The thorough analysis presented here highlights the effectiveness of silicon elements in enhancing the mechanical characteristics of the shaft propeller made of aluminum alloy, which bodes well for future developments in ship propulsion technology.